Prognosis of Extracapsular Spread of Cervical Lymph Node Metastases in Nasopharyngeal Carcinoma - Yin, Xue; Lv, Lu; Pan, Xin-Bin (Frontiers in Oncology, 2020)
Purpose: To identify the prognosis of the extracapsular spread (ECS) of cervical lymph node metastases in nasopharyngeal carcinoma (NPC). Materials and methods: NPC patients were extracted from the Surveillance, Epidemiology, and End Results (SEER) database from 2004 to 2016. Pathologically confirmed World Health Organization type I, II and III NPC patients with complete ECS data of cervical lymph node metastases were investigated. The included patients were divided into non-ECS and ECS groups. Ten-year overall survival (OS) and cancer-specific survival (CSS) were compared between the two groups using the Kaplan-Meier method and propensity score matching analyses. Results: A total of 625 patients were included. The ECS group included 99 (15.84%) patients. The non-ECS group included 526 (84.16%) patients. The 10-year OS (50.2% vs 35.8%, P < 0.001) and CSS (64.8% vs 45.7%, P < 0.001) were better in the non-ECS group than in the ECS group in the unmatched cohort. Propensity score matching analyses revealed favorable 10-year OS (52.7% vs 35.8%, P = 0.008) and CSS (61.2% vs 45.7%, P = 0.008) in the non-ECS group with respect to the ECS group. Age, sex, race, AJCC stage, and ECS (hazard ratio [HR] = 1.71, 95% confidence interval [CI]: 1.14-2.57, P = 0.010) were independent prognostic factors for OS. Age, sex, AJCC stage, and ECS (HR = 1.91, 95% CI: 1.21-3.01, P = 0.005) were independent prognostic factors for CSS. Conclusion: This study indicated that ECS is a prognostic risk factor for NPC. Further studies should be performed to verify the results due to the limitations of the SEER database.